2011
DOI: 10.1387/ijdb.103243eo
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin and tenascin-C: accomplices in vascular morphogenesis during development and tumor growth

Abstract: In addition to soluble factors, the extracellular matrix (ECM) also plays a vital role in normal vasculogenesis and in the pathological angiogenesis of many disease states. Here we will review what is known about the role of the ECM molecules fibronectin and tenascin-C in the vasculature and highlight a potential collaborative interplay between these molecules in developmental and tumorigenic angiogenesis. We will address the evolution of these modular proteins, their cellular interactions and how they become … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
96
0
3

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 106 publications
(101 citation statements)
references
References 175 publications
(202 reference statements)
2
96
0
3
Order By: Relevance
“…106 Upon destruction of blood vessels with 2 anti-angiogenic drugs in a well-established insulinoma model and in a murine xenograft tumor model with Lewis lung carcinoma cells it was observed that revascularization occurred along so called matrix sleeves positive for collagen IV, interpreted as remnants of vascular basement membranes. 107 Whether these matrix sleeves contained tenascin-C had not been addressed but is likely since tenascin-C is found to be highly expressed around newly formed tumor blood vessels (reviewed in 19 , 2 ). Given its instrumental role in promoting tumor angiogenesis 4,13 it is an intriguing possibility that tenascin-C may also promote revascularization upon anti angiogenic treatment.…”
Section: Potential Role Of Tenascin-c In Tumor Relapse and Resistancementioning
confidence: 99%
See 2 more Smart Citations
“…106 Upon destruction of blood vessels with 2 anti-angiogenic drugs in a well-established insulinoma model and in a murine xenograft tumor model with Lewis lung carcinoma cells it was observed that revascularization occurred along so called matrix sleeves positive for collagen IV, interpreted as remnants of vascular basement membranes. 107 Whether these matrix sleeves contained tenascin-C had not been addressed but is likely since tenascin-C is found to be highly expressed around newly formed tumor blood vessels (reviewed in 19 , 2 ). Given its instrumental role in promoting tumor angiogenesis 4,13 it is an intriguing possibility that tenascin-C may also promote revascularization upon anti angiogenic treatment.…”
Section: Potential Role Of Tenascin-c In Tumor Relapse and Resistancementioning
confidence: 99%
“…Both ECM molecules bind to each other and are frequently coexpressed in cancer tissue in particular around newly formed blood vessels. 19 Tenascin-C was shown to counteract cell adhesion to fibronectin through competition with syndecan-4 binding to fibronectin. 108 Thus both molecules might play a role as accomplices in tumor progression.…”
Section: Potential Role Of Tenascin-c In Tumor Relapse and Resistancementioning
confidence: 99%
See 1 more Smart Citation
“…This collection of functions is reflected in the wide ranging consequences of genetic deletion of tenascin-C in mice. Reported abnormalities include reduced FN during dermal wound healing, 4 hyperactivity, 5 reduced kidney regeneration, 6 reduced haematopoiesis, 7 increased tumor monocyte population, 8 abnormal tumor organization and angiogenesis, 9,10 and aberrant immune responses, [11][12][13] among many others (reviewed in 14,15 ). Genetic variation at the human tenascin-C gene locus is associated with 6-fold increase in risk of Achilles tendon injury, 16 non-syndromic hearing loss, 17 and increased risk of developing adult asthma.…”
mentioning
confidence: 99%
“…Tenascin C (TNC) is an ECM glycoprotein frequently upregulated in several inflammatory diseases as well as in neoplastic pathologies; this protein is highly involved in the regulation of cellular migration, proliferation, invasion, and angiogenesis (van Obberghen-Schilling et al, 2011). TNC exists in numerous isoforms that are the result of alternative splicings, and are heterogeneously expressed in both normal and neoplastic tissues (Leprini et al, 1994).…”
Section: Tenascin Cmentioning
confidence: 99%